To Evaluate the Frequency, Gender and Age-Related Distribution of Papillary Urothelial Carcinoma (Medical Forum Monthly, 2024)
Objective: To evaluate the frequency, gender and age-related distribution of papillary urothelial carcinoma.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Pathology, Basic Medical Science Institutes, Jinnah Postgraduates Medical Center Karachi from January 2009 to December 2016.Materials and Methods: Total numbers of 247 cases of papillary urothelial carcinoma were reviewed and morphological diagnosis done on H&E; information regarding gender and age were recorded from archives. The data analyzed by SPSS version 21.Results: Frequency of papillary urothelial carcinoma was 6.8%. Out of 247 cases 85.42% in male and 14.57% in female with male: female ratio of 5.8:1. Relatively more common in 5th & 6th decade’s i-e 59% as compared to other age groups. Mean and median age of papillary urothelial carcinoma was 57.62 and 65 years noted.Conclusion: Frequency of urothelial carcinoma was 6.8%. Amongst 247 cases 211 were in male gender and 36 cases in female sex with M: F ratio of 5.8:1. While according to age 85, 60, 57, 24, 17 and 04 cases were in 5th, 6th, 4th, > 7th, 3rd and less than 3rd decades, minimum and maximum age was 22 and 90 years respectively.